Real-time Product Availability Information with Passive NFC Tag System for Offline Shops - Erlina, Tati (Computer Engineering Departement, Universitas Komputer Indonesia, 2024)
Offering a seamless shopping experience is essential in today's cutthroat retail environment. This paper describes a system built to tell customers about product availability in offline stores, explicitly addressing the issues related to customer reluctance and the store's physical space restrictions. The system was designed, observed, and tested to evaluate its performance. According to the findings, the system can recognize various NFC tag types at reading distances of up to 3.5 cm, 1.5 cm, and 2 cm for a card, keychain, and sticker kinds, respectively. In an average of 3.39 seconds, the server and microcontroller can establish a connection to send and receive responses from the server. Additionally, the system has a 100% success record in displaying precise product stock data based on the chosen size and color. Furthermore, the system has a 100% success rate in telling registered from unregistered NFC tags. The internet network's speed also impacts updating database data, with quicker internet connections being processed first. In conclusion, the system's effectiveness demonstrates its potential to be used in retail settings to give customers real-time product availability tracking.